Analisis Resistensi Pegawai Dalam Kebijakan Jam Kerja di Dinas Pendidikan Kota Gunungsitoli - Zai, Agusdarmawati; Hidayat Waruwu, Meiman; Telaumbanua, Eliagus; Beniah Ndraha, Ayler (DINASTI RESEARCH, 2024)
This research aims to analyze employee resistance to the working hour policy at the Gunungsitoli City Education Office, which has an impact on the effectiveness of public services. The research method used is descriptive qualitative, with data collection through observation, interviews, and documentation. The results show that employee resistance is mainly influenced by a strong organizational culture, incompatibility with the new policy, and lack of employee participation in the policy planning process. The study found that such resistance resulted in decreased work discipline, which negatively impacted the quality of public services. The discussion of the results underscores the importance of inclusive and transparent management strategies in designing and implementing policies, to improve employee compliance and reduce resistance. The conclusion of this study confirms that active involvement of employees in policy planning and participatory approaches can minimize resistance and improve organizational performance and the quality of public services at the Gunungsitoli City Education Office.